Pengaruh E-Commerce Dan Sustainability Marketing Terhadap Keputusan Pembelian Produk Makanan Ramah Lingkungan Masyarakat Palopo - Umi Kalsum; Hesti Ardianti; Nurjannah; Nurfatima Azzahra; Eka Feby Wahyuningtyas (Movere Journal, 2026)
This study aims to analyze the influence of e-commerce and sustainability marketing on consumers' purchasing decisions regarding environmentally friendly food products in Palopo. The study employed a quantitative research approach. Data were collected through an online questionnaire distributed to 120 randomly selected respondents. After the data passed the validity and reliability tests, they were analyzed using multiple linear regression with SPSS. The results indicate that, partially, both e-commerce and sustainability marketing have a positive and significant effect on consumers' purchasing decisions for environmentally friendly food products